1983
DOI: 10.1007/bf00409141
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidative destruction of chloroplasts and its consequences for cytosolic enzyme levels and plant development

Abstract: Mustard (Sinapis alba L.) seedlings were grown in the presence of herbicides (Difunon, Norflurazon) which inhibit carotenoid synthesis without affecting development, in darkness or in continuous far-red light. In strong white light (12,000 lx) the cotyledons of the herbicide-treated seedlings did not contain normal chloroplasts, but only small chlorophyll-free rudiments whose internal structure had almost disappeared. The plastid marker enzyme NADP-dependent glyceraldehyde-3-phosphate dehydrogenase was almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…We used the herbicide NF (4-chloro-5-(methylamino)-2-(a,a,a-trifluorom-tolyl)-3-(2H)-pyridazinone; Sandoz 9789) to induce photooxidative destruction of chloroplasts in WL (22,24,27). NF inhibits synthesis of carotenoid pigments that protect Chl from photobleaching in strong light.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We used the herbicide NF (4-chloro-5-(methylamino)-2-(a,a,a-trifluorom-tolyl)-3-(2H)-pyridazinone; Sandoz 9789) to induce photooxidative destruction of chloroplasts in WL (22,24,27). NF inhibits synthesis of carotenoid pigments that protect Chl from photobleaching in strong light.…”
mentioning
confidence: 99%
“…NF inhibits synthesis of carotenoid pigments that protect Chl from photobleaching in strong light. In photobleached chloroplasts, Chl content is greatly reduced, as are plastid rRNAs, mRNAs, and proteins (14,20,24). The primary effects of photooxidation are confined to the plastids.…”
mentioning
confidence: 99%
“…These observation confirmed results reporter by Irving and coworkers (1999) who showed that norflurazon significantly increased the elongation growth of etiolated maize coleoptiles in comparison with untreated control. Thus, the effect of this chemical on plants is highly dependent on the light conditions and the differences concern mainly the structure of plastids (Pardo and Schiff, 1980;Reib et al, 1983;Di Baccio et al, 2002). Reib et al (1983) showed that cotyledons of norflurazontreated mustard seedlings grown in strong white light did not contain normal chloroplasts, but only small chlorophyll-free rudiments with completely destroyed internal structure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effect of this chemical on plants is highly dependent on the light conditions and the differences concern mainly the structure of plastids (Pardo and Schiff, 1980;Reib et al, 1983;Di Baccio et al, 2002). Reib et al (1983) showed that cotyledons of norflurazontreated mustard seedlings grown in strong white light did not contain normal chloroplasts, but only small chlorophyll-free rudiments with completely destroyed internal structure. Treatment of etiolated bean leaves with this herbicide had only little effect on the formation of normal prothylakoids and prolamellar bodies (Pardo and Schiff, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation